Relevansi Filsafat Ilmu di Era Revolusi Industri 5.0: Sebuah Analisis Fenomenologis - Retisfa Khairanis; Muhammad Aldi (Universitas Serambi Mekkah, 2024)
The Industrial Revolution 5.0 has brought significant paradigm shifts in various aspects of life, including the way we understand and produce knowledge. This research explores the relevance of philosophy of science in the context of the Industrial Revolution 5.0 through a comprehensive literature analysis. Using a philosophical hermeneutic approach, this study examines the evolution of the philosophy of science paradigm, the epistemological and ontological challenges that arise, and the ethical and social implications of new technologies. The findings show that philosophy of science faces the need to adapt to the epistemological shifts brought about by big data and artificial intelligence, as well as develop an ethical framework that is responsive to contemporary technological dilemmas. The research also reveals the transformation of scientific methodology, from traditional hypothesis-deductive approaches to data-driven models, as well as the important role of computational simulation and human-machine collaboration in scientific discovery. Furthermore, the study underscores the crucial role of philosophy of science in facilitating interdisciplinary dialog, developing evaluation frameworks for new technologies, and preparing society for the radical changes brought about by the Industrial Revolution 5.0. This research concludes that philosophy of science not only remains relevant, but is becoming increasingly important in the digital age, with significant potential to contribute to the development of more ethical technologies and a more comprehensive understanding of reality in the era of the Industrial Revolution 5.0.. Keywords:Philosophy of Science, Industrial Revolution 5.0, Digital Epistemology